Environment-friendly high-performance concrete admixture and preparation method thereof
By adding specific combinations of admixtures to the concrete, the problem of termites building nests in buildings is solved, and the crack resistance of concrete is improved, achieving effective removal of termites and improving the stability of concrete during construction and use.
Patent Information
- Application Number
- CN202411821041.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In construction environments, it is difficult to ensure that there are no colonies in the soil, which can nest in buildings and destroy the wooden structure.
It provides an environmentally friendly high-performance concrete admixture, and the preparation raw materials include insect odorants, insect repellents, thermal conductivity and anti-cracking agents. The termite repellent and cracking resistance of concrete is improved through the combination of mantis powder, sterilized shrew urine, neem leaf powder, neem leaf powder, copper powder and epoxy resin particles.
Effectively drive away termites, avoid them from nesting in buildings, and improve the crack resistance of concrete, preventing cracks from occurring during use.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmentally friendly high-performance concrete, and specifically relates to an environmentally friendly high-performance concrete admixture and a preparation method thereof. Background Art
[0002] Environmentally friendly high-performance concrete is a concrete material that further enhances its environmental friendliness on the basis of high-performance concrete.
[0003] However, it is difficult to ensure that there are no termite colonies in the soil in a construction environment. After the construction of a building is completed, termite colonies may build nests in small cracks in the building and cause damage to the wooden structures in subsequent buildings. Summary of the invention
[0004] The purpose of the present invention is to provide an environmentally friendly high-performance concrete admixture and a preparation method thereof in order to solve the above-mentioned problems.
[0005] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0006] The present invention provides an environmentally friendly high-performance concrete admixture, wherein the raw materials for its preparation include, by weight: 3-7 parts of an insect odor agent, 4-10 parts of an insect repellent, 2-6 parts of a thermal conductor, and 5-7 parts of an anti-cracking agent;
[0007] Wherein, the raw materials for preparing the insect odor agent include, by weight: 1-3 parts of mantis powder and 3-8 parts of bactericidal shrew urine;
[0008] Wherein, the raw materials for preparing the insect repellent include, by weight: 2-4 parts of neem leaf powder and 3-6 parts of neem leaf powder;
[0009] Wherein, by weight, the raw materials for preparing the thermal conductor include: 1-2 parts of copper ore powder and 1-3 parts of epoxy resin particles.
[0010] As a further optimization scheme of the present invention, the preparation process of the mantis powder is as follows: (i) freeze-drying and dehydrating the mantis corpse to obtain a freeze-dried mantis corpse; and (ii) grinding the freeze-dried mantis corpse to obtain mantis powder.
[0011] As a further optimization scheme of the present invention, the preparation process of the shrew urine is as follows: (i) pouring the shrew urine into a sealed bag for sealing; (ii) placing the sealed bag in a cooking box for cooking, controlling the temperature to 80-100° C., and controlling the time to 20-30 min; (iii) taking the sealed bag out of the cooking box, standing it at room temperature to cool down, and obtaining sterilized shrew urine.
[0012] As a further optimization scheme of the present invention, the preparation process of the neem leaf powder is as follows: (i) washing the neem leaves and then drying and dehydrating them; (ii) grinding the neem leaves to obtain the neem leaf powder;
[0013] The preparation process of the neem leaf powder is as follows: (i) washing the neem leaves and then drying and dehydrating them; and (ii) grinding the neem leaf powder to obtain the neem leaf powder.
[0014] As a further optimization scheme of the present invention, the preparation process of the copper ore powder is as follows: (i) rinsing and drying the chalcopyrite; (ii) heating the chalcopyrite at a high temperature, controlling the heating to 1200-1500° C., and controlling the heating time to 20-30 min to obtain high-temperature chalcopyrite; (iii) placing the high-temperature chalcopyrite in cold water, controlling the cold water temperature to 2-4° C., and controlling the cooling time to 30-40 min to obtain quenched chalcopyrite; (iv) grinding the quenched chalcopyrite to obtain copper ore powder.
[0015] As a further optimization scheme of the present invention, the raw materials for preparing the anti-cracking agent include, by weight: 2-3 parts of glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and 4-6 parts of flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm.
[0016] As a further optimization scheme of the present invention, the preparation process of the anti-cracking agent is: glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm are uniformly mixed and stirred, the stirring speed is controlled to 20-30 r / min, and the stirring time is controlled to 5-10 min to obtain the anti-cracking agent.
[0017] The present invention also provides a method for preparing an environmentally friendly high-performance concrete admixture, comprising the following steps:
[0018] S1, uniformly mixing the mantis powder and the sterilized shrew urine, controlling the stirring speed to 10-30 r / min, and controlling the stirring time to 5-10 min, to obtain an insect odor agent;
[0019] S2, uniformly mixing the neem leaf powder and the neem leaf powder, controlling the stirring speed to 10-30 r / min, and controlling the stirring time to 5-10 min, to obtain an insect repellent;
[0020] S3, uniformly mixing the insect odor agent and the insect repellent, controlling the stirring speed to 20-30 r / min, and controlling the stirring time to 5-10 min to obtain a mixture;
[0021] S4, melting the epoxy resin particles at high temperature, then evenly scattering the copper ore powder on the epoxy resin solution, and then using a granulator to make thermal conductive particles with a diameter of 0.1 mm, thereby obtaining a thermal conductive agent;
[0022] S5, heating the thermal conductive agent to control the temperature to 50-70° C., then evenly sprinkling the mixture on the thermal conductive agent, vibrating the thermal conductive agent for a controlled time of 1-3 minutes, and then naturally cooling the mixture so that the mixture adheres to the thermal conductive agent to obtain composite particles;
[0023] S6, uniformly mixing and stirring the composite particles, glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm, and flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm, controlling the stirring speed to 5-15 / min, and controlling the stirring time to 10-20 min, to obtain an environmentally friendly high-performance concrete admixture.
[0024] The beneficial effects of the present invention are as follows: the insect odor agent prepared from mantis powder and bactericidal shrew urine, the insect repellent prepared from neem leaf powder and neem leaf powder have a good termite repelling effect when used in combination, and the thermal conductor prepared from copper ore powder and epoxy resin particles conducts sunlight heat conduction to enhance the activity of the insect odor agent and the insect repellent, thereby achieving the effect of effectively repelling termites during the concrete pouring process and in a short period of time thereafter, helping to force termites to change their nests, and avoiding termites from nesting in small cracks in buildings and damaging wooden structures in subsequent buildings as much as possible; the anti-cracking agent prepared from glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm helps to enhance the mutual adhesion and flexibility of the concrete, and avoids as much as possible the cracking phenomenon of the environmentally friendly high-performance concrete caused by the prepared environmentally friendly high-performance concrete admixture when added to the environmentally friendly high-performance concrete for use. DETAILED DESCRIPTION
[0025] The present application is described in further detail below. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technicians in this field can make some non-essential improvements and adjustments to the present application based on the above application content.
[0026] 1. Materials
[0027] Unless otherwise specified, the methods used in the present invention are conventional methods known to those skilled in the art, and the reagents and other materials used are commercially available products unless otherwise specified.
[0028] (1) In the present invention;
[0029] The water in the present invention is pure water.
[0030] 2. Embodiment
[0031] Example 1
[0032] An environmentally friendly high-performance concrete admixture, wherein the raw materials for its preparation include, by weight: 3 parts of an insect odor agent, 4 parts of an insect repellent, 2 parts of a thermal conductive agent, and 5 parts of an anti-cracking agent;
[0033] Wherein, the raw materials for preparing the insect odor agent include, by weight: 1 part of mantis powder and 3 parts of bactericidal shrew urine;
[0034] Wherein, the raw materials for preparing the insect repellent include, by weight: 2 parts of neem leaf powder and 3 parts of neem leaf powder;
[0035] Wherein, the raw materials for preparing the thermal conductor include, by weight: 1 part of copper ore powder and 1 part of epoxy resin particles;
[0036] Wherein, the raw materials for preparing the anti-cracking agent include, by weight: 2 parts of glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and 4 parts of flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm;
[0037] The preparation method of the above-mentioned environmentally friendly high-performance concrete admixture comprises the following steps:
[0038] Mantis powder: (i) freeze-drying and dehydrating a mantis corpse to obtain a freeze-dried mantis corpse; (ii) grinding the freeze-dried mantis corpse to obtain mantis powder;
[0039] Shrew urine: (i) pouring shrew urine into a sealed bag for sealing; (ii) placing the sealed bag in a cooking box for cooking, controlling the temperature to 80° C. for 20 min; (iii) taking the sealed bag out of the cooking box, and allowing it to stand at room temperature to cool down, thereby obtaining sterilized shrew urine;
[0040] Neem leaf powder: (i) washing neem leaves and then drying and dehydrating them; (ii) grinding the neem leaves to obtain neem leaf powder;
[0041] Neem leaf powder: (i) washing neem leaves and then drying and dehydrating them; (ii) grinding the neem leaf powder to obtain neem leaf powder;
[0042] Copper ore powder: (i) washing and drying the chalcopyrite; (ii) heating the chalcopyrite at a high temperature, controlling the heating temperature to 1200°C, controlling the heating time to 20 minutes, and obtaining high-temperature chalcopyrite; (iii) placing the high-temperature chalcopyrite in cold water, controlling the cold water temperature to 2°C, and controlling the cooling time to 30 minutes, and obtaining quenched chalcopyrite; (iv) grinding the quenched chalcopyrite to obtain copper ore powder;
[0043] The mantis powder and the sterilized shrew urine were uniformly mixed and stirred, the stirring speed was controlled to be 10 r / min, and the stirring time was controlled to be 5 min to obtain an insect odor agent;
[0044] The neem leaf powder and the neem leaf powder are uniformly mixed and stirred, the stirring speed is controlled to be 10 r / min, and the stirring time is controlled to be 5 min to obtain an insect repellent;
[0045] The insect odor agent and the insect repellent are uniformly mixed and stirred, the stirring speed is controlled to be 20r / min, and the stirring time is controlled to be 5min to obtain a mixture;
[0046] The epoxy resin particles are melted at high temperature, and then the copper ore powder is evenly scattered on the epoxy resin solution, and then a granulator is used to make thermal conductive particles with a diameter of 0.1 mm to obtain a thermal conductive agent;
[0047] The thermal conductive agent is heated to a temperature of 50° C., and then the mixture is evenly sprinkled on the thermal conductive agent, and the thermal conductive agent is vibrated for a controlled time of 1 minute, and then naturally cooled, so that the mixture adheres to the thermal conductive agent to obtain composite particles;
[0048] Anti-cracking agent: glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm are uniformly mixed and stirred, and the stirring speed is controlled to be 20 r / min and the stirring time is controlled to be 5 min to obtain an anti-cracking agent;
[0049] The composite particles and the anti-cracking agent are uniformly mixed and stirred, the stirring speed is controlled to be 5 / min, and the stirring time is controlled to be 10min, so as to obtain an environmentally friendly high-performance concrete admixture.
[0050] Example 2
[0051] An environmentally friendly high-performance concrete admixture, wherein the raw materials for its preparation include, by weight: 5 parts of an insect odorant, 7 parts of an insect repellent, 4 parts of a thermal conductor, and 6 parts of an anti-cracking agent;
[0052] Wherein, the raw materials for preparing the insect odor agent include, by weight: 2 parts of mantis powder and 6 parts of bactericidal shrew urine;
[0053] Wherein, the raw materials for preparing the insect repellent include, by weight: 3 parts of neem leaf powder and 5 parts of neem leaf powder;
[0054] Wherein, the raw materials for preparing the thermal conductor include, by weight: 1.5 parts of copper ore powder and 2 parts of epoxy resin particles;
[0055] Wherein, the raw materials for preparing the anti-cracking agent include, by weight: 2.5 parts of glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and 5 parts of flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm;
[0056] The preparation method of the above-mentioned environmentally friendly high-performance concrete admixture comprises the following steps:
[0057] Mantis powder: (i) freeze-drying and dehydrating a mantis corpse to obtain a freeze-dried mantis corpse; (ii) grinding the freeze-dried mantis corpse to obtain mantis powder;
[0058] Shrew urine: (i) pouring shrew urine into a sealed bag for sealing; (ii) placing the sealed bag in a cooking box for cooking, controlling the temperature to 90° C. for 25 min; (iii) taking the sealed bag out of the cooking box, and letting it stand at room temperature to cool down, thereby obtaining sterilized shrew urine;
[0059] Neem leaf powder: (i) washing neem leaves and then drying and dehydrating them; (ii) grinding the neem leaves to obtain neem leaf powder;
[0060] Neem leaf powder: (i) washing neem leaves and then drying and dehydrating them; (ii) grinding the neem leaf powder to obtain neem leaf powder;
[0061] Copper ore powder: (i) washing and drying the chalcopyrite; (ii) heating the chalcopyrite at a high temperature, controlling the heating temperature to 1350°C, controlling the heating time to 25 minutes, and obtaining high-temperature chalcopyrite; (iii) placing the high-temperature chalcopyrite in cold water, controlling the cold water temperature to 3°C, and controlling the cooling time to 35 minutes, and obtaining quenched chalcopyrite; (iv) grinding the quenched chalcopyrite to obtain copper ore powder;
[0062] The mantis powder and the sterilized shrew urine were uniformly mixed and stirred, the stirring speed was controlled to be 20 r / min, and the stirring time was controlled to be 8 min to obtain an insect odor agent;
[0063] The neem leaf powder and the neem leaf powder are uniformly mixed and stirred, the stirring speed is controlled to be 20r / min, and the stirring time is controlled to be 8min to obtain an insect repellent;
[0064] The insect odor agent and the insect repellent are uniformly mixed and stirred, the stirring speed is controlled to be 25r / min, and the stirring time is controlled to be 8min to obtain a mixture;
[0065] The epoxy resin particles are melted at high temperature, and then the copper ore powder is evenly scattered on the epoxy resin solution, and then a granulator is used to make thermal conductive particles with a diameter of 0.1 mm to obtain a thermal conductive agent;
[0066] The thermal conductive agent is heated to a temperature of 60° C. Then, the mixture is evenly sprinkled on the thermal conductive agent, and the thermal conductive agent is vibrated for a controlled time of 2 minutes, and then naturally cooled so that the mixture adheres to the thermal conductive agent to obtain composite particles;
[0067] Anti-cracking agent: glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm are uniformly mixed and stirred, the stirring speed is controlled to be 25 r / min, and the stirring time is controlled to be 8 min to obtain an anti-cracking agent;
[0068] The composite particles and the anti-cracking agent are uniformly mixed and stirred, the stirring speed is controlled to be 10 / min, and the stirring time is controlled to be 15min, so as to obtain an environmentally friendly high-performance concrete admixture.
[0069] Example 3
[0070] An environmentally friendly high-performance concrete admixture, wherein the raw materials for its preparation include, by weight: 7 parts of an insect odor agent, 10 parts of an insect repellent, 6 parts of a thermal conductive agent, and 7 parts of an anti-cracking agent;
[0071] Wherein, the raw materials for preparing the insect odor agent include, by weight: 3 parts of mantis powder and 8 parts of bactericidal shrew urine;
[0072] Wherein, the raw materials for preparing the insect repellent include, by weight: 4 parts of neem leaf powder and 6 parts of neem leaf powder;
[0073] Wherein, the raw materials for preparing the thermal conductor include, by weight: 2 parts of copper ore powder and 3 parts of epoxy resin particles;
[0074] Wherein, the raw materials for preparing the anti-cracking agent include, by weight: 3 parts of glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and 6 parts of flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm;
[0075] The preparation method of the above-mentioned environmentally friendly high-performance concrete admixture comprises the following steps:
[0076] Mantis powder: (i) freeze-drying and dehydrating a mantis corpse to obtain a freeze-dried mantis corpse; (ii) grinding the freeze-dried mantis corpse to obtain mantis powder;
[0077] Shrew urine: (i) pouring shrew urine into a sealed bag for sealing; (ii) placing the sealed bag in a cooking box for cooking, controlling the temperature to be 100° C., and controlling the time to be 30 min; (iii) taking the sealed bag out of the cooking box, and allowing it to stand at room temperature to cool down, thereby obtaining sterilized shrew urine;
[0078] Neem leaf powder: (i) washing neem leaves and then drying and dehydrating them; (ii) grinding the neem leaves to obtain neem leaf powder;
[0079] Neem leaf powder: (i) washing neem leaves and then drying and dehydrating them; (ii) grinding the neem leaf powder to obtain neem leaf powder;
[0080] Copper ore powder: (i) washing and drying the chalcopyrite; (ii) heating the chalcopyrite at a high temperature, controlling the heating temperature to 1500°C and the heating time to 30 minutes to obtain high-temperature chalcopyrite; (iii) placing the high-temperature chalcopyrite in cold water, controlling the cold water temperature to 4°C and the cooling time to 40 minutes to obtain quenched chalcopyrite; (iv) grinding the quenched chalcopyrite to obtain copper ore powder
[0081] The mantis powder and the sterilized shrew urine were uniformly mixed and stirred, the stirring speed was controlled to be 30 r / min, and the stirring time was controlled to be 10 min to obtain an insect odor agent;
[0082] The neem leaf powder and the neem leaf powder are uniformly mixed and stirred, the stirring speed is controlled to be 30r / min, and the stirring time is controlled to be 10min to obtain an insect repellent;
[0083] The insect odor agent and the insect repellent are uniformly mixed and stirred, the stirring speed is controlled to be 30r / min, and the stirring time is controlled to be 10min to obtain a mixture;
[0084] The epoxy resin particles are melted at high temperature, and then the copper ore powder is evenly scattered on the epoxy resin solution, and then a granulator is used to make thermal conductive particles with a diameter of 0.1 mm to obtain a thermal conductive agent;
[0085] The thermal conductive agent is heated to a temperature of 70° C., and then the mixture is evenly sprinkled on the thermal conductive agent, and the thermal conductive agent is vibrated for a controlled time of 3 minutes, and then naturally cooled so that the mixture adheres to the thermal conductive agent to obtain composite particles;
[0086] Anti-cracking agent: glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm are uniformly mixed and stirred, the stirring speed is controlled to be 30 r / min, and the stirring time is controlled to be 10 min to obtain an anti-cracking agent;
[0087] The composite particles and the anti-cracking agent are uniformly mixed and stirred, the stirring speed is controlled to be 15 / min, and the stirring time is controlled to be 20min, so as to obtain an environmentally friendly high-performance concrete admixture.
[0088] Comparative Example 1
[0089] An environmentally friendly high-performance concrete admixture, the raw materials for its preparation include, by weight: 10 parts of insect repellent, 6 parts of thermal conductive agent, and 6 parts of anti-cracking agent;
[0090] Wherein, the raw materials for preparing the insect repellent include, by weight: 3 parts of neem leaf powder and 5 parts of neem leaf powder;
[0091] Wherein, the raw materials for preparing the thermal conductor include, by weight: 1.5 parts of copper ore powder and 2 parts of epoxy resin particles;
[0092] Wherein, the raw materials for preparing the anti-cracking agent include, by weight: 2.5 parts of glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and 5 parts of flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm;
[0093] The preparation method of the above-mentioned environmentally friendly high-performance concrete admixture comprises the following steps:
[0094] Neem leaf powder: (i) washing neem leaves and then drying and dehydrating them; (ii) grinding the neem leaves to obtain neem leaf powder;
[0095] Neem leaf powder: (i) washing neem leaves and then drying and dehydrating them; (ii) grinding the neem leaf powder to obtain neem leaf powder;
[0096] Copper ore powder: (i) washing and drying the chalcopyrite; (ii) heating the chalcopyrite at a high temperature, controlling the heating temperature to 1350°C, controlling the heating time to 25 minutes, and obtaining high-temperature chalcopyrite; (iii) placing the high-temperature chalcopyrite in cold water, controlling the cold water temperature to 3°C, and controlling the cooling time to 35 minutes, and obtaining quenched chalcopyrite; (iv) grinding the quenched chalcopyrite to obtain copper ore powder;
[0097] The neem leaf powder and the neem leaf powder are uniformly mixed and stirred, the stirring speed is controlled to be 20r / min, and the stirring time is controlled to be 8min to obtain an insect repellent;
[0098] The epoxy resin particles are melted at high temperature, and then the copper ore powder is evenly scattered on the epoxy resin solution, and then a granulator is used to make thermal conductive particles with a diameter of 0.1 mm to obtain a thermal conductive agent;
[0099] The thermal conductor is heated to a temperature of 60° C., and then, an insect repellent is evenly sprinkled on the thermal conductor, and the thermal conductor is vibrated for a controlled time of 2 minutes, and then naturally cooled, so that the insect repellent adheres to the thermal conductor, thereby obtaining composite particles;
[0100] Anti-cracking agent: glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm are uniformly mixed and stirred, the stirring speed is controlled to be 25 r / min, and the stirring time is controlled to be 8 min to obtain an anti-cracking agent;
[0101] The mixture and the anti-cracking agent are uniformly mixed and stirred, the stirring speed is controlled to be 10 / min, and the stirring time is controlled to be 15min, so as to obtain an environmentally friendly high-performance concrete admixture.
[0102] Comparative Example 2
[0103] An environmentally friendly high-performance concrete admixture, wherein the raw materials for its preparation include, by weight: 9 parts of insect odor agent, 7 parts of thermal conductive agent, and 6 parts of anti-cracking agent;
[0104] Wherein, the raw materials for preparing the insect odor agent include, by weight: 2 parts of mantis powder and 6 parts of bactericidal shrew urine;
[0105] Wherein, the raw materials for preparing the thermal conductor include, by weight: 1.5 parts of copper ore powder and 2 parts of epoxy resin particles;
[0106] Wherein, the raw materials for preparing the anti-cracking agent include, by weight: 2.5 parts of glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and 5 parts of flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm;
[0107] The preparation method of the above-mentioned environmentally friendly high-performance concrete admixture comprises the following steps:
[0108] Mantis powder: (i) freeze-drying and dehydrating a mantis corpse to obtain a freeze-dried mantis corpse; (ii) grinding the freeze-dried mantis corpse to obtain mantis powder;
[0109] Shrew urine: (i) pouring shrew urine into a sealed bag for sealing; (ii) placing the sealed bag in a cooking box for cooking, controlling the temperature to 90° C. for 25 min; (iii) taking the sealed bag out of the cooking box, and letting it stand at room temperature to cool down, thereby obtaining sterilized shrew urine;
[0110] Copper ore powder: (i) washing and drying the chalcopyrite; (ii) heating the chalcopyrite at a high temperature, controlling the heating temperature to 1350°C, controlling the heating time to 25 minutes, and obtaining high-temperature chalcopyrite; (iii) placing the high-temperature chalcopyrite in cold water, controlling the cold water temperature to 3°C, and controlling the cooling time to 35 minutes, and obtaining quenched chalcopyrite; (iv) grinding the quenched chalcopyrite to obtain copper ore powder;
[0111] The mantis powder and the sterilized shrew urine were uniformly mixed and stirred, the stirring speed was controlled to be 20 r / min, and the stirring time was controlled to be 8 min to obtain an insect odor agent;
[0112] The epoxy resin particles are melted at high temperature, and then the copper ore powder is evenly scattered on the epoxy resin solution, and then a granulator is used to make thermal conductive particles with a diameter of 0.1 mm to obtain a thermal conductive agent;
[0113] The thermal conductor is heated to a temperature of 60° C., and then the insect odorant is evenly sprinkled on the thermal conductor, and the thermal conductor is vibrated for a controlled time of 2 minutes, and then naturally cooled, so that the insect odorant adheres to the thermal conductor to obtain composite particles;
[0114] Anti-cracking agent: glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm are uniformly mixed and stirred, the stirring speed is controlled to be 25 r / min, and the stirring time is controlled to be 8 min to obtain an anti-cracking agent;
[0115] The mixture and the anti-cracking agent are uniformly mixed and stirred, the stirring speed is controlled to be 10 / min, and the stirring time is controlled to be 15min, so as to obtain an environmentally friendly high-performance concrete admixture.
[0116] Comparative Example 3
[0117] An environmentally friendly high-performance concrete admixture, the raw materials for its preparation include, by weight: 6 parts of insect odor agent, 10 parts of insect repellent, and 6 parts of anti-cracking agent;
[0118] Wherein, the raw materials for preparing the insect odor agent include, by weight: 2 parts of mantis powder and 6 parts of bactericidal shrew urine;
[0119] Wherein, the raw materials for preparing the insect repellent include, by weight: 3 parts of neem leaf powder and 5 parts of neem leaf powder;
[0120] Wherein, the raw materials for preparing the anti-cracking agent include, by weight: 2.5 parts of glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and 5 parts of flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm;
[0121] The preparation method of the above-mentioned environmentally friendly high-performance concrete admixture comprises the following steps:
[0122] Mantis powder: (i) freeze-drying and dehydrating a mantis corpse to obtain a freeze-dried mantis corpse; (ii) grinding the freeze-dried mantis corpse to obtain mantis powder;
[0123] Shrew urine: (i) pouring shrew urine into a sealed bag for sealing; (ii) placing the sealed bag in a cooking box for cooking, controlling the temperature to 90° C. for 25 min; (iii) taking the sealed bag out of the cooking box, and letting it stand at room temperature to cool down, thereby obtaining sterilized shrew urine;
[0124] Neem leaf powder: (i) washing neem leaves and then drying and dehydrating them; (ii) grinding the neem leaves to obtain neem leaf powder;
[0125] Neem leaf powder: (i) washing neem leaves and then drying and dehydrating them; (ii) grinding the neem leaf powder to obtain neem leaf powder;
[0126] Copper ore powder: (i) washing and drying the chalcopyrite; (ii) heating the chalcopyrite at a high temperature, controlling the heating temperature to 1350°C, controlling the heating time to 25 minutes, and obtaining high-temperature chalcopyrite; (iii) placing the high-temperature chalcopyrite in cold water, controlling the cold water temperature to 3°C, and controlling the cooling time to 35 minutes, and obtaining quenched chalcopyrite; (iv) grinding the quenched chalcopyrite to obtain copper ore powder;
[0127] The mantis powder and the sterilized shrew urine were uniformly mixed and stirred, the stirring speed was controlled to be 20 r / min, and the stirring time was controlled to be 8 min to obtain an insect odor agent;
[0128] The neem leaf powder and the neem leaf powder are uniformly mixed and stirred, the stirring speed is controlled to be 20r / min, and the stirring time is controlled to be 8min to obtain an insect repellent;
[0129] The insect odor agent and the insect repellent are uniformly mixed and stirred, the stirring speed is controlled to be 25r / min, and the stirring time is controlled to be 8min to obtain a mixture;
[0130] Anti-cracking agent: glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm are uniformly mixed and stirred, the stirring speed is controlled to be 25 r / min, and the stirring time is controlled to be 8 min to obtain an anti-cracking agent;
[0131] The mixture and the anti-cracking agent are uniformly mixed and stirred, the stirring speed is controlled to be 10 / min, and the stirring time is controlled to be 15min, so as to obtain an environmentally friendly high-performance concrete admixture.
[0132] Comparative Example 4
[0133] An environmentally friendly high-performance concrete admixture, wherein the raw materials for its preparation include, by weight: 5 parts of an insect odorant, 7 parts of an insect repellent, 4 parts of a thermal conductor, and 6 parts of an anti-cracking agent;
[0134] Wherein, the raw materials for preparing the insect odor agent include, by weight: 2 parts of mantis powder and 6 parts of bactericidal shrew urine;
[0135] Wherein, the raw materials for preparing the insect repellent include, by weight: 3 parts of neem leaf powder and 5 parts of neem leaf powder;
[0136] Wherein, the raw materials for preparing the thermal conductor include, by weight: 1.5 parts of copper ore powder and 2 parts of epoxy resin particles;
[0137] Wherein, the anti-cracking agent is specifically a flax fiber with a diameter of 0.01 mm and a length of 1 mm, in parts by weight;
[0138] The preparation method of the above-mentioned environmentally friendly high-performance concrete admixture comprises the following steps:
[0139] Mantis powder: (i) freeze-drying and dehydrating a mantis corpse to obtain a freeze-dried mantis corpse; (ii) grinding the freeze-dried mantis corpse to obtain mantis powder;
[0140] Shrew urine: (i) pouring shrew urine into a sealed bag for sealing; (ii) placing the sealed bag in a cooking box for cooking, controlling the temperature to 90° C. for 25 min; (iii) taking the sealed bag out of the cooking box, and letting it stand at room temperature to cool down, thereby obtaining sterilized shrew urine;
[0141] Neem leaf powder: (i) washing neem leaves and then drying and dehydrating them; (ii) grinding the neem leaves to obtain neem leaf powder;
[0142] Neem leaf powder: (i) washing neem leaves and then drying and dehydrating them; (ii) grinding the neem leaf powder to obtain neem leaf powder;
[0143] Copper ore powder: (i) washing and drying the chalcopyrite; (ii) heating the chalcopyrite at a high temperature, controlling the heating temperature to 1350°C, controlling the heating time to 25 minutes, and obtaining high-temperature chalcopyrite; (iii) placing the high-temperature chalcopyrite in cold water, controlling the cold water temperature to 3°C, and controlling the cooling time to 35 minutes, and obtaining quenched chalcopyrite; (iv) grinding the quenched chalcopyrite to obtain copper ore powder;
[0144] The mantis powder and the sterilized shrew urine were uniformly mixed and stirred, the stirring speed was controlled to be 20 r / min, and the stirring time was controlled to be 8 min to obtain an insect odor agent;
[0145] The neem leaf powder and the neem leaf powder are uniformly mixed and stirred, the stirring speed is controlled to be 20r / min, and the stirring time is controlled to be 8min to obtain an insect repellent;
[0146] The insect odor agent and the insect repellent are uniformly mixed and stirred, the stirring speed is controlled to be 25r / min, and the stirring time is controlled to be 8min to obtain a mixture;
[0147] The epoxy resin particles are melted at high temperature, and then the copper ore powder is evenly scattered on the epoxy resin solution, and then a granulator is used to make thermal conductive particles with a diameter of 0.1 mm to obtain a thermal conductive agent;
[0148] The thermal conductive agent is heated to a temperature of 60° C. Then, the mixture is evenly sprinkled on the thermal conductive agent, and the thermal conductive agent is vibrated for a controlled time of 2 minutes, and then naturally cooled so that the mixture adheres to the thermal conductive agent to obtain composite particles;
[0149] The composite particles and the anti-cracking agent are uniformly mixed and stirred, the stirring speed is controlled to be 10 / min, and the stirring time is controlled to be 15min, so as to obtain an environmentally friendly high-performance concrete admixture.
[0150] Comparative Example 5
[0151] An environmentally friendly high-performance concrete admixture, wherein the raw materials for its preparation include, by weight: 5 parts of an insect odorant, 7 parts of an insect repellent, 4 parts of a thermal conductor, and 6 parts of an anti-cracking agent;
[0152] Wherein, the raw materials for preparing the insect odor agent include, by weight: 2 parts of mantis powder and 6 parts of bactericidal shrew urine;
[0153] Wherein, the raw materials for preparing the insect repellent include, by weight: 3 parts of neem leaf powder and 5 parts of neem leaf powder;
[0154] Wherein, the raw materials for preparing the thermal conductor include, by weight: 1.5 parts of copper ore powder and 2 parts of epoxy resin particles;
[0155] Wherein, the anti-cracking agent is specifically glass fiber with a diameter of 0.01 mm and a length of 1 mm, in parts by weight;
[0156] The preparation method of the above-mentioned environmentally friendly high-performance concrete admixture comprises the following steps:
[0157] Mantis powder: (i) freeze-drying and dehydrating a mantis corpse to obtain a freeze-dried mantis corpse; (ii) grinding the freeze-dried mantis corpse to obtain mantis powder;
[0158] Shrew urine: (i) pouring shrew urine into a sealed bag for sealing; (ii) placing the sealed bag in a cooking box for cooking, controlling the temperature to 90° C. for 25 min; (iii) taking the sealed bag out of the cooking box, and letting it stand at room temperature to cool down, thereby obtaining sterilized shrew urine;
[0159] Neem leaf powder: (i) washing neem leaves and then drying and dehydrating them; (ii) grinding the neem leaves to obtain neem leaf powder;
[0160] Neem leaf powder: (i) washing neem leaves and then drying and dehydrating them; (ii) grinding the neem leaf powder to obtain neem leaf powder;
[0161] Copper ore powder: (i) washing and drying the chalcopyrite; (ii) heating the chalcopyrite at a high temperature, controlling the heating temperature to 1350°C, controlling the heating time to 25 minutes, and obtaining high-temperature chalcopyrite; (iii) placing the high-temperature chalcopyrite in cold water, controlling the cold water temperature to 3°C, and controlling the cooling time to 35 minutes, and obtaining quenched chalcopyrite; (iv) grinding the quenched chalcopyrite to obtain copper ore powder;
[0162] The mantis powder and the sterilized shrew urine were uniformly mixed and stirred, the stirring speed was controlled to be 20 r / min, and the stirring time was controlled to be 8 min to obtain an insect odor agent;
[0163] The neem leaf powder and the neem leaf powder are uniformly mixed and stirred, the stirring speed is controlled to be 20r / min, and the stirring time is controlled to be 8min to obtain an insect repellent;
[0164] The insect odor agent and the insect repellent are uniformly mixed and stirred, the stirring speed is controlled to be 25r / min, and the stirring time is controlled to be 8min to obtain a mixture;
[0165] The epoxy resin particles are melted at high temperature, and then the copper ore powder is evenly scattered on the epoxy resin solution, and then a granulator is used to make thermal conductive particles with a diameter of 0.1 mm to obtain a thermal conductive agent;
[0166] The thermal conductive agent is heated to a temperature of 60° C. Then, the mixture is evenly sprinkled on the thermal conductive agent, and the thermal conductive agent is vibrated for a controlled time of 2 minutes, and then naturally cooled so that the mixture adheres to the thermal conductive agent to obtain composite particles;
[0167] The composite particles and the anti-cracking agent are uniformly mixed and stirred, the stirring speed is controlled to be 10 / min, and the stirring time is controlled to be 15min, so as to obtain an environmentally friendly high-performance concrete admixture.
[0168] Comparative Example 6: An environmentally friendly high-performance concrete admixture, the raw materials for its preparation include, by weight: 6.8 parts of insect odor agent, 9.6 parts of insect repellent, and 5.6 parts of thermal conductive agent;
[0169] Wherein, the raw materials for preparing the insect odor agent include, by weight: 2 parts of mantis powder and 6 parts of bactericidal shrew urine;
[0170] Wherein, the raw materials for preparing the insect repellent include, by weight: 3 parts of neem leaf powder and 5 parts of neem leaf powder;
[0171] Wherein, the raw materials for preparing the thermal conductor include, by weight: 1.5 parts of copper ore powder and 2 parts of epoxy resin particles;
[0172] The preparation method of the above-mentioned environmentally friendly high-performance concrete admixture comprises the following steps:
[0173] Mantis powder: (i) freeze-drying and dehydrating a mantis corpse to obtain a freeze-dried mantis corpse; (ii) grinding the freeze-dried mantis corpse to obtain mantis powder;
[0174] Shrew urine: (i) pouring shrew urine into a sealed bag for sealing; (ii) placing the sealed bag in a cooking box for cooking, controlling the temperature to 90° C. for 25 min; (iii) taking the sealed bag out of the cooking box, and letting it stand at room temperature to cool down, thereby obtaining sterilized shrew urine;
[0175] Neem leaf powder: (i) washing neem leaves and then drying and dehydrating them; (ii) grinding the neem leaves to obtain neem leaf powder;
[0176] Neem leaf powder: (i) washing neem leaves and then drying and dehydrating them; (ii) grinding the neem leaf powder to obtain neem leaf powder;
[0177] Copper ore powder: (i) washing and drying the chalcopyrite; (ii) heating the chalcopyrite at a high temperature, controlling the heating temperature to 1350°C, controlling the heating time to 25 minutes, and obtaining high-temperature chalcopyrite; (iii) placing the high-temperature chalcopyrite in cold water, controlling the cold water temperature to 3°C, and controlling the cooling time to 35 minutes, and obtaining quenched chalcopyrite; (iv) grinding the quenched chalcopyrite to obtain copper ore powder;
[0178] The mantis powder and the sterilized shrew urine were uniformly mixed and stirred, the stirring speed was controlled to be 20 r / min, and the stirring time was controlled to be 8 min to obtain an insect odor agent;
[0179] The neem leaf powder and the neem leaf powder are uniformly mixed and stirred, the stirring speed is controlled to be 20r / min, and the stirring time is controlled to be 8min to obtain an insect repellent;
[0180] The insect odor agent and the insect repellent are uniformly mixed and stirred, the stirring speed is controlled to be 25r / min, and the stirring time is controlled to be 8min to obtain a mixture;
[0181] The epoxy resin particles are melted at high temperature, and then the copper ore powder is evenly scattered on the epoxy resin solution, and then a granulator is used to make thermal conductive particles with a diameter of 0.1 mm to obtain a thermal conductive agent;
[0182] The thermal conductor is heated and the temperature is controlled at 60°C. Then, the mixture is evenly sprinkled on the thermal conductor and the thermal conductor is vibrated for a controlled time of 2 minutes. Then, it is naturally cooled so that the mixture adheres to the thermal conductor to obtain composite particles, which are environmentally friendly high-performance concrete admixtures.
[0183] 3. Test Experiment
[0184] 3.1. Anti-insect experiment
[0185] 1) Experimental materials: 600 kg of environmentally friendly high-performance concrete (including cement, sand, and gravel) (the mass ratio of cement, sand, and gravel is 1:2.13:4.23);
[0186] 60 kg of water;
[0187] 60 1*1*1m 3 A removable container;
[0188] 60 5*5*5m 3 A container containing 20 kg of soil;
[0189] 6,000 termites.
[0190] 2) Experimental steps:
[0191] ① Place 100 termites in a container containing 20 kg of soil and place it outdoors for 7 days;
[0192] ②600KG of environmentally friendly high-performance concrete and 60KG of water are divided into 60 portions, each portion contains 10KG of environmentally friendly high-performance concrete and 1KG of water;
[0193] ③ Take 5 kg of each of the environmentally friendly high-performance concrete admixtures prepared in Examples 1-3 and Comparative Examples 1-3, and divide the 5 kg of environmentally friendly high-performance concrete admixtures into 10 portions, each portion weighing 0.5 kg;
[0194] ④ Place a removable container in the center of each container containing 20 kg of soil;
[0195] ⑤ Evenly mix 0.5 kg of environmentally friendly high-performance concrete admixture, 10 kg of environmentally friendly high-performance concrete and 1 kg of water, pour them into a demoulding container and let them stand for forming. Then, take out 60 concrete blocks, remove the demoulding container, and place the concrete blocks in the original position of the demoulding container;
[0196] ⑥ The number of termites escaping from the container containing 20 kg of soil was recorded by a camera for 5 days, and the average value was taken for the environmentally friendly high-performance concrete containing the environmentally friendly high-performance concrete admixture prepared in the same embodiment or the same comparative example, and the record was as follows Table 1:
[0197] project Number of escapees Example 1 75 Example 2 88 Example 3 73 Comparative Example 1 50 Comparative Example 2 39 Comparative Example 3 48
[0198] As can be seen from the above table, compared with Example 1, Example 3 and Comparative Examples 1-3, the environmentally friendly high-performance concrete admixture prepared in Example 2 has a larger number of termites fleeing. It can be seen that the insect odor agent prepared from mantis powder and bactericidal shrew urine, the insect repellent prepared from neem leaf powder and neem leaf powder have a good termite repelling effect when used in combination, and the thermal conductor prepared from copper ore powder and epoxy resin particles conducts heat through sunlight, thereby enhancing the activity of the insect odor agent and the insect repellent, thereby achieving the effect of effectively repelling termites.
[0199] 3.2. Crack resistance test
[0200] 1) Experimental materials: 4000 kg of environmentally friendly high-performance concrete (including cement, sand, and gravel) (the mass ratio of cement, sand, and gravel is 1:2.13:4.23);
[0201] 400 kg of water;
[0202] 400 1*1*1m 3 A removable container;
[0203] 2) Experimental steps:
[0204] ①400KG of environmentally friendly high-performance concrete and 40KG of water are divided into 400 portions, each portion contains 10KG of environmentally friendly high-performance concrete and 1KG of water;
[0205] ② Take 5 kg of each of the environmentally friendly high-performance concrete admixtures prepared in Example 2 and Comparative Examples 4-6, and divide the 5 kg of environmentally friendly high-performance concrete admixtures into 10 portions, each portion weighing 0.5 kg;
[0206] ③ Evenly mix 0.5 kg of environmentally friendly high-performance concrete admixture, 10 kg of environmentally friendly high-performance concrete and 1 kg of water, pour them into a demoulding container and let them stand for forming. Then, take out 400 concrete blocks and observe whether there are cracks in the concrete blocks.
[0207] ④ The crack rate of the environmentally friendly high-performance concrete containing the environmentally friendly high-performance concrete admixture prepared in the same embodiment or the same comparative example is calculated and recorded in the following Table 2:
[0208] project Crack rate Example 2 0% Comparative Example 4 1% Comparative Example 5 2% Comparative Example 6 4%
[0209] As can be seen from the above table, compared with Comparative Examples 4-6, in the prepared environmentally friendly high-performance concrete admixture in Example 2, the anti-cracking agent prepared from glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm helps to improve the mutual adhesion and flexibility inside the concrete, and tries to avoid the environmentally friendly high-performance concrete from cracking when the prepared environmentally friendly high-performance concrete admixture is added to the environmentally friendly high-performance concrete for use.
[0210] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. An environmentally friendly high-performance concrete admixture, characterized in that: The raw materials for its preparation include, by weight: 3-7 parts of insect odor agent, 4-10 parts of insect repellent, 2-6 parts of thermal conductive agent, and 5-7 parts of anti-cracking agent; Wherein, the raw materials for preparing the insect odor agent include, by weight: 1-3 parts of mantis powder and 3-8 parts of bactericidal shrew urine; Wherein, the raw materials for preparing the insect repellent include, by weight: 2-4 parts of neem leaf powder and 3-6 parts of neem leaf powder; Wherein, by weight, the raw materials for preparing the thermal conductor include: 1-2 parts of copper ore powder and 1-3 parts of epoxy resin particles.
2. An environmentally friendly high-performance concrete admixture according to claim 1, characterized in that: The preparation process of the mantis powder is as follows: (i) freeze-drying and dehydrating the mantis corpse to obtain a freeze-dried mantis corpse; and (ii) grinding the freeze-dried mantis corpse to obtain the mantis powder.
3. An environmentally friendly high-performance concrete admixture according to claim 1, characterized in that: The preparation process of the shrew urine is as follows: (i) pouring the shrew urine into a sealed bag for sealing; (ii) placing the sealed bag in a cooking box for cooking, controlling the temperature to be 80-100° C., and controlling the time to be 20-30 min; (iii) taking the sealed bag out of the cooking box, and letting it stand at room temperature to cool down, thereby obtaining sterilized shrew urine.
4. The environmentally friendly high-performance concrete admixture according to claim 1, characterized in that: The preparation process of the neem leaf powder is as follows: (i) washing the neem leaves and then drying and dehydrating them; (ii) grinding the neem leaves to obtain the neem leaf powder; The preparation process of the neem leaf powder is as follows: (i) washing the neem leaves and then drying and dehydrating them; and (ii) grinding the neem leaf powder to obtain the neem leaf powder.
5. The environmentally friendly high-performance concrete admixture according to claim 1, characterized in that: The preparation process of the copper ore powder is as follows: (i) washing and drying the chalcopyrite; (ii) heating the chalcopyrite at a high temperature, controlling the heating temperature to 1200-1500° C., controlling the heating time to 20-30 min, and obtaining the high-temperature chalcopyrite; (iii) placing the high-temperature chalcopyrite in cold water, controlling the cold water temperature to 2-4° C., controlling the cooling time to 30-40 min, and obtaining the quenched chalcopyrite; (iv) grinding the quenched chalcopyrite to obtain the copper ore powder.
6. The environmentally friendly high-performance concrete admixture according to claim 1, characterized in that: The raw materials for preparing the anti-cracking agent include, by weight: 2-3 parts of glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and 4-6 parts of flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm.
7. An environmentally friendly high-performance concrete admixture according to claim 6, characterized in that: The preparation process of the anti-cracking agent is as follows: glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm and flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm are uniformly mixed and stirred, the stirring speed is controlled to be 20-30 r / min, and the stirring time is controlled to be 5-10 min to obtain the anti-cracking agent.
8. A method for preparing the environmentally friendly high-performance concrete admixture according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, uniformly mixing the mantis powder and the sterilized shrew urine, controlling the stirring speed to 10-30 r / min, and controlling the stirring time to 5-10 min, to obtain an insect odor agent; S2, uniformly mixing the neem leaf powder and the neem leaf powder, controlling the stirring speed to 10-30 r / min, and controlling the stirring time to 5-10 min, to obtain an insect repellent; S3, uniformly mixing the insect odor agent and the insect repellent, controlling the stirring speed to 20-30 r / min, and controlling the stirring time to 5-10 min to obtain a mixture; S4, melting the epoxy resin particles at high temperature, then evenly scattering the copper ore powder on the epoxy resin solution, and then using a granulator to make thermal conductive particles with a diameter of 0.1 mm, thereby obtaining a thermal conductive agent; S5, heating the thermal conductive agent to control the temperature to 50-70° C., then evenly sprinkling the mixture on the thermal conductive agent, vibrating the thermal conductive agent for a controlled time of 1-3 minutes, and then naturally cooling the mixture so that the mixture adheres to the thermal conductive agent to obtain composite particles; S6, uniformly mixing and stirring the composite particles, glass fiber filaments with a diameter of 0.01 mm and a length of 1 mm, and flax fiber filaments with a diameter of 0.01 mm and a length of 1 mm, controlling the stirring speed to 5-15 / min, and controlling the stirring time to 10-20 min, to obtain an environmentally friendly high-performance concrete admixture.